Anti-inflammatory Activity of Different Extracts of Leaves of Alstonia scholaris Linn. - Yogendra Singh Shakya*, Dr. Gajendra Singh Rathor, Gaja Ram Sirvi (International Journal of Advanced Science and Technology, 2019)
AIM- The aim of the present investigation is to find out the Anti-inflammatory Activity of Different Extracts of Leaves of Alstonia scholaris Linn. MATERIAL & METHODS- All the plant materials were dried under shade and subjected to coarse powder for extraction process. Accurately weighed quantity of leaf powder of Alstonia scholaris were extracted using 95 % ethanol by soxhlet apparatus for 72 h. Qualitative chemical tests of ethanolic extracts were subjected to various chemical tests to detect various phytoconstituents. The acute oral toxicity studies were carried out according to the guidelines set by the Organization for Economic Co-operation and Development (OECD), revised draft guideline 423. Inflammation was induced by 0.1 mL of 1% suspension of carrageenan into hind paw of rat by sub planter route. Treatments of all fractions were given 1 h prior to administration of carrageenan. Paw volume was measured with digital plethysmograph at 0, 1, 2, 3, 4 and 5th h after injection. RESULTS- The preliminary phytochemical analysis revealed that different active constituent present in different extracts such as carbohydrates, proteins, amino acids, fat, oils, steroids, terpenoids, glycosides, alkaloids, tannins and other phenolics compounds. No toxic effects were observed at a higher dose of 2000 mg/kg body weight of Wistar rats. Hence, 1/ 10th dose was selected as effective dose or therapeutic dose. The cut off value of 200 and 1/5 dose double of 400 mg/kg were selected for anti-inflammatory activity. The ethanolic extract (200 & 400 mg/kg) significantly (p <0.01, p><0.001) inhibited carrageenan induced rat paw edema as compared to control group. Maximum inhibition of rat paw edema was observed with ethanolic extract (400 mg/kg) at the end of 5 th h when compared to control group. CONCLUSION- These components could serve as lead molecules for development of prospective anti-inflammatory agents. Further detailed studies are required to elucidate the exact mechanism based on molecular and genetic level responsible for antiinflammatory activity. >